Structure factor for an icosahedral quasicrystal within a statistical approach. Issue 3 (11th March 2015) - Strzalka, Radoslaw; Buganski, Ireneusz; Wolny, Janusz
<x xml:space="preserve">Abstract</x> This paper describes a detailed derivation of a structural model for an icosahedral quasicrystal based on a primitive icosahedral tiling (three‐dimensional Penrose tiling) within a statistical approach. The average unit cell concept, where all calculations are performed in three‐dimensional physical space, is used as an alternative to higher‐dimensional analysis. Comprehensive analytical derivation of the structure factor for a primitive icosahedral lattice with monoatomic decoration (atoms placed in the nodes of the lattice only) presents in detail the idea of the statistical approach to icosahedral quasicrystal structure modelling and confirms its full agreement with the higher‐dimensional description. The arbitrary decoration scheme is also discussed. The complete structure‐factor formula for arbitrarily decorated icosahedral tiling is derived and its correctness is proved. This paper shows in detail the concept of a statistical approach applied to the problem of icosahedral quasicrystal modelling.